Effectiveness of Integrated Nutrition Intervention Programs in Stunting Prevention in the First 1000 Days of Life - Rumani , Risza Presty (Pt. Anagata Sembagi Education, 2025)
Stunting is one of the main nutritional problems that affect the physical and cognitive development of children under the age of two, especially in the First 1,000 Days of Life (HPK) period. The Integrated Nutrition Intervention Program, which combines specific interventions such as nutritional supplementation with sensitive interventions such as improved sanitation and access to clean water, has been shown to be effective in reducing the prevalence of stunting. This study aims to measure the effectiveness of the Integrated Nutrition Intervention Program in the prevention of stunting in children aged 0–24 months in Indonesia, with a focus on strengthening the role of agents of change at the community level. The method used in this study is a quantitative approach with experimental design, where data is collected through surveys and interviews with mothers in the areas that have implemented the program. The results of the study showed that this program succeeded in reducing the prevalence of stunting by 8.1% in Trenggalek Regency and 1.5% in Bima City after the implementation of integrated nutrition interventions. These findings show that community engagement, empowerment of health cadres, and cross-sectoral integration are key factors in the success of the program. This study provides recommendations to expand the implementation of integrated nutrition intervention programs nationally, as well as strengthen the role of communities in maintaining the sustainability of programs to achieve national and global targets in stunting reduction by 2025